Clinical Impact of Consolidative and Salvage Radiotherapy for Lymph Node Metastasis in Upper Urinary Tract Urothelial Carcinoma. (22nd April 2018) - Kondo, Hideyuki; Shirotake, Suguru; Okabe, Takashi; Makino, Soichi; Nishimoto, Koshiro; Oyama, Masafumi
Abstract : A 75-year-old Japanese male was referred to our institution for the evaluation of a left ureteral tumor in the ureterovesical junction. Computed tomography and pathologic examination under ureteroscopy revealed an invasive left ureteral urothelial carcinoma with left obturator nodal metastasis without distant metastasis. First, the patient underwent systemic chemotherapy (gemcitabine and cisplatin chemotherapy). We then performed left radical nephroureterectomy and extended lymph node dissection. Pathological examination revealed that the tumor was a high-grade invasive urothelial carcinoma with left common iliac and pelvic lymph node metastasis (pT3N2). Unfortunately, metastases appeared in the common iliac and para-aortic lymph nodes immediately after the operation; therefore, the previous first-line chemotherapy was readministered and second-line chemotherapy (gemcitabine and paclitaxel chemotherapy) was also performed. We also performed consolidative radiotherapy and salvage radiotherapy (boost, 20 Gy/10 fractions to the inferior para-aortic, and left common iliac regions containing swollen lymph nodes). The patient has shown no evidence of recurrence or metastasis even approximately 4 years after the initial diagnosis of advanced UUT-UC with lymph node metastasis. Our case suggests that consolidative or salvage radiotherapy combined with surgery and chemotherapy may provide clinical benefit for selected cases of advanced UUT-UC with lymph node metastasis.